Enhancing Hospital Service Quality Through Strategic and Operational Excellence Focused on Patient Satisfaction: The Case of Indonesia - Renaldus Iwan Sumarta; Iman Sudirman; Jaja Suteja; Horas Djulius; Mohammad Sofyan (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2025)
Introduction: Hospitals, functioning both as public service institutions and business entities, must prioritize patient satisfaction to ensure the sustainability of their services. This study explores the relationships among operational strategy, operational competence, quality culture, and service quality, as well as their combined impact on patient satisfaction in Indonesian hospitals. Methods: This study employed a quantitative approach using a survey method. Data were collected from 300 respondents, comprising medical and non-medical staff, across four hospitals in Jambi Province. Structural Equation Modeling (SEM) was utilized for data analysis, enabling an in-depth examination of both direct and indirect relationships among the variables. Results: The findings revealed that operational strategy and operational competence significantly influenced quality culture and service quality. Additionally, quality culture and service quality collectively impacted patient satisfaction, highlighting the critical roles of these factors in enhancing hospital performance. Notably, service quality had the strongest direct effect on patient satisfaction, while quality culture contributed to sustaining these improvements over time. Conclusions: These findings underscore the essential role of strategic alignment and operational excellence in achieving higher levels of patient satisfaction. The study provides valuable insights for hospital management and policymakers in developing countries, advocating for the integration of strategic planning and competency development to enhance healthcare delivery systems and improve patient outcomes.